2017
DOI: 10.11648/j.ajmse.20170206.15
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Analysis of the General Electric Company of Libya

Abstract: Abstract:In this study, the current situation of the General Electric Company of Libya (GECOL) was assessed by measuring the total and partial service productivity from 2006 to 2014, using a proposed measurement model, which was constructed based on a well-known model adopted for analysis of productivity which satisfies the basic productivity concept. Two phases were used in this study to measure the company's productivity. In phase one, productivity was measured using the outputs data based on the electricity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In (Frefer et al 2017) researchers assessed the current situation of the General Electric Company of Libya (GECOL) by measuring the total and partial service productivity from 2006 to 2014 and two phases were used in the study to measure the company's productivity. In phase one, productivity was measured using the outputs data based on the electricity delivered and in phase two; an attempt was made to find the actual output and the results showed that there was a decline in the productivity of the company in all years of the study period and that the company's overall performance during the study period was generally poor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In (Frefer et al 2017) researchers assessed the current situation of the General Electric Company of Libya (GECOL) by measuring the total and partial service productivity from 2006 to 2014 and two phases were used in the study to measure the company's productivity. In phase one, productivity was measured using the outputs data based on the electricity delivered and in phase two; an attempt was made to find the actual output and the results showed that there was a decline in the productivity of the company in all years of the study period and that the company's overall performance during the study period was generally poor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modelling and simulation techniques of manufacturing may assist to build an understanding of the processes and may also help in recognizing and testing ways that lead to maximum production efficiency [3,31]. The ability to accurately identify all inputs and outputs as financial value highly impacts the process of constructing the productivity measurement model [4]. Therefore, several types of simulation modelling software exist in the market to improve and develop complicated manufacturing systems [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Productivity is the key to greater competitiveness, as it is critical to the profitability of most construction projects. Besides, according to Frefer; productivity is one of the essential aspects of the erection industry, which helps its survival and growth [11]. Wilcox argued that improving productivity is a crucial concern for any profit-oriented association and effective change of resources into marketable products, and it determines business productivity [27].…”
Section: Introductionmentioning
confidence: 99%